Produção de recobrimentos metálicos a partir de ligas de ferro amorfizáveis - Silva, Ana Martha Branquinho e (Universidade Federal de São Carlos, 2011)
The aim of this work was to study the production of metal coatings from amorphous alloy Fe-25Cr-7Ni-4,5B (wt.%), with special focus on mechanical and microstructure properties. Initially, preliminary studies were made through the production of ribbons and bulks of metallic alloys Fe-25Cr-7Ni-XB (X = 3.5, 4.5, 5.5 wt.%) for the evaluation of amorphous phase formation. The alloy showed the best results was used in the production of the following samples by spray forming process: deposits used to assess the main process parameters involved; coatings manufactured using pre-layer of nickel alloys, whose aim was to allow the adhesion of particles on the substrate; and powders, that were sieved and separated into specific grain sizes. These powders, together with the same alloy powders produced by grinding through the process of highenergy milling, were sent to the Ogramac company for the manufacture of coatings via thermal spraying process HVOF (high velocity oxygen fuel). The characterization of all samples was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The mechanical properties were evaluated by hardness and wear tests. Although the preliminary results of the samples have shown good prospects regarding the formation of amorphous phases, these phases were not identified in deposits, coatings and powders with particle size less than 45 μm produced by spray forming. However, these coatings exhibited efficient adhesion to the substrate, which is a highly advantageous in the production equipment DEMAUFSCar. The coatings produced by thermal spraying processes have shown interesting results concerning the microstructure obtained in addition to higher values of hardness and wear properties when compared to conventional materials.
Production of metallic coatings based on amorphous iron alloys
Keywords: Engenharia de materiais; Materiais amorfos; Solidificação rápida; Conformação por spray; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA